Development of Phonics Method through Magic Board to Stimulate Reading Skill of Children Aged 5 – 6 Years - Humaeroh, Dini; Suryani, Yuni Dwi (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to develop a phonics-based learning method using a